Family functionality and burden of family caregivers of users with mental disorders - Jaciquely José da Costa Andrade; Andrea Cristina Oliveira Silva; Iracema da Silva Frazão; Jaqueline Galdino Albuquerque Perrelli; Thassia Thame de Moura Silva; Ana Márcia Tenório Souza Cavalcanti (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to verify the difference of mean or median in the scores of family functionality and burden of family caregivers of people with mental disorders. Methods: cross-sectional study carried out in a Psychosocial Care Center with 61 family caregivers. Instruments were used for sociodemographic characterization, care process, Family Apgar Index and Family Burden Interview Schedule. Mean/median difference tests were adopted. Results: women with mental disorders and the presence of children in the home decreased the median of the family Apgar score. Difficulty in the relationship between caregiver/user, nervousness/tension, physical aggression and agitation of patients increased the global average of subjective burden. Conclusions: nursing interventions to reduce burden and promote family functionality should prioritize caregivers of women with mental disorders, assist them in managing troublesome behaviors and raising awareness of family nucleus to co-responsibility for caring for sick people, especially in families with children who demand daily care.